Profiles of diphtheria cases in children in Hasan Sadikin Hospital, West Java - Iskandar, Safira Atya; Setiabudi, Djatnika; Tarigan, Rodman; Alam, Anggraini; Afriandi, Irvan (Indonesian Pediatric Society, 2024)
Background Diphtheria cases continue to be reported in Indonesia, which has long been one of the countries with the highest number of diphtheria cases worldwide. One of Indonesia's province with the highest annual diphtheria cases is West Java. Dr. Hasan Sadikin General Hospital (RSHS) is one of the tertiary referral hospitals in Bandung, West Java, that treats several diphtheria cases annually. No study focused on the clinical characteristics of diphtheria cases in children admitted to RSHS between 2017 and 2021 yet. Therefore, this study sought to analyze that. Objective To find out the profiles of children < 18-year-old with diphtheria admitted in RSHS between 2017-2021. Methods This descriptive, cross-sectional study reviewed the medical records of diphtheria patients 0 to 18-year-old who were admitted to RSHS between year 2017 and 2021. Results Out of 45 subjects, 76% were males. The median of age was eight years old, ranging from 2 to 17 years. Most patients lived in urban areas and had normal anthropometry status, although some showed abnormal findings. The data showed that 44% had more than 3 days of onset until admission to the hospital, and the median length of stay was 9 days. The clinical characteristics showed that 91% of patients had pseudomembrane, also present with cough, common cold, hoarseness, stridor, and bull’s neck. As many as 44% of patients did not have complete basic immunization status. Complications found were airway obstructions, myocarditis, and sepsis, and 2 deaths were reported. Conclusion Pseudomembrane was found in the majority of patients. Most patients were over five years of age, and almost half number of the patients did not have complete basic immunization status, indicating the need for improved immunization and booster coverage.